FRI0362 Angiogenic t cell expansion correlates with severity of peripheral vascular damage in systemic sclerosis. (15th June 2017) - Manetti, M; Pratesi, S; Romano, E; Rosa, I; Martiradonna, A; Bellando-Randone, S; Guiducci, S; Ibba-Manneschi, L; Maggi, E; Matucci-Cerinic, M
Abstract : Background: The mechanisms underlying endothelial cell injury and defective vascular repair in systemic sclerosis (SSc) remain unclear. Recent studies suggest that a novel T cell subset, the so-called angiogenic T (Tang) cells, may have an important impact on the repair of damaged endothelium. Tang cells are characterised by the co-expression of CD3, CD31 (platelet-endothelial cell adhesion molecule-1) and CXCR4 (or CD184, receptor for the CXC chemokine stromal cell-derived factor-1 (SDF-1)/CXCL12). Tang cells may promote the formation of new blood vessels and endothelial repair by stimulating the function and differentiation of endothelial progenitor cells possibly through the secretion of proangiogenic cytokines, thus fostering postnatal vasculogenesis. Objectives: This study aimed to analyse the Tang cell population in relation to disease-related peripheral vascular features in SSc patients. Methods: Tang cells (CD3 + CD31 + CXCR4 + ) were quantified by flow cytometry in peripheral blood samples from 39 patients with SSc and 18 matched healthy controls (HC). CD3 + CD31 + CXCR4 + Tang cells were expressed as a percentage of total CD3 + T cells. Circulating levels of SDF-1α were assessed in paired serum samples by immunoassay. Skin sections from patients with early diffuse cutaneous SSc (n=7) and HC (n=6) were subjected to CD3/CD31 and CD3/CXCR4 double immunofluorescence staining. Results: The percentage of circulating Tang cells was not different between the whole SSc patient cohort (median 29.9, interquartile range (IQR) 22.3–36.2) and HC (median 25.2, IQR 23.3–33.5). Subgroup analysis revealed that Tang cells were significantly increased in SSc patients with digital ulcers (DU) (median 35.5, IQR 32.2–42.5) compared either with SSc patients without DU (median 23.3, IQR 18.5–26.6) or with HC (p<0.0001 for both). Furthermore, Tang cell percentage was significantly higher in SSc patients with "late" nailfold videocapillaroscopy (NVC) pattern (median 34.9, IQR 25.0–42.0) than in those with "early"/"active" NVC patterns (median 26.5, IQR 20.4–32.9) and in HC (p=0.01 and p=0.04, respectively). No difference in circulating Tang cell counts was found when comparing either SSc patients without DU or patients with "early"/"active" NVC patterns and HC. In SSc peripheral blood, the percentage of Tang cells was inversely correlated to the levels of SDF-1α (Spearman's rho = -0.59, p<0.0001). Immunohistologic assessment of SSc skin sections revealed the presence of Tang cells in perivascular inflammatory infiltrates. Conclusions: Our findings demonstrate for the first time that Tang cells are expanded in patients with SSc displaying most severe peripheral vascular complications. Such an expansion may be an ineffective attempt to compensate the need for increased angiogenesis and endothelial progenitor cell function. In SSc, Tang cells might represent a potentially useful biomarker reflecting peripheral vascular damage severity. Further studies are required to clarify the function of Tang cells and investigate the mechanisms responsible for their change in SSc. Disclosure of Interest: None declared